A History of Visconti’s Army in the Fourteenth Century: an Unpublished Register of Loans Granted to Mercenaries between 1340 and 1388 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The following article starts from the analysis of an unpublished register, which dates back to 1428, and it is currently kept in the Archive of the Milan Cathedral's Venerable Factory. It deals with a long series of loan, among which 123 loans, that had been granted to mercenaries between 1340 and 1388, stand out. The collected information enables us to get a full picture of the composition of the Visconti army in the 14th century. Great attention should be paid to 151 names of soldiers of fortune, who served the Milan's Lords and maintained economic relations with 11 wealthy citizens, which decided to invest their money in subsidies to mercenary troops, in times of crisis. Taking the shortage of sources into account, the significant numbers examined in the register lead us to think about the great deal of money which was put into circulation by the Visconti's military machine. Furthermore, analyzing these numbers helps us studying how the Visconti succeeded in financing battles, even when their expansionistic ambitions exceeded their economic resources, by remaining militarily active, on several fronts, for extended periods of time.
Keywords: Mercenaries; Visconti; 14th Century; The Archive of the Milan Cathedral's Venerable Factory; Loan